Developing novel photocatalytic cementitious permeable pavements for depollution of contaminants and impurities in urban cities - Tota-Maharaj, Kiran; Coleman, Nichola (International Conference “Environmental Engineering”, 2017)
Photocatalyst such as Titanium Dioxide (TiO2) has been recently introduced as a nanoparticle into cementitious permeable pavements. Combining photocatalytic compounds within concrete permeable pavements can aid with depollution of several contaminants found in urban water streams and air impurities. This paper presents research carried out at the University of Greenwich, UK using photocatalytic concrete with varying percentages of TiO2 (0 %, 1% and 5%) to assess the levels depollution which can be achieved. Concrete samples were testing against the degradation of 2, 4-Dichlorophenoxyacetic Acid, a harmful chemical found in herbicides. This advanced oxidation process can aid in the reduction of urban pollution from an air and water perspective, improving sustainability for urban cities. Self-cleaning benefits of photocatalytic concrete permeable pavements can be used to keep urban infrastructure cleaner and more aesthetically pleasing. Experimental tests were carried out on the characterisation of inorganics through X-Ray diffraction and Fourier Transform Infrared Spectroscopy to ensure that the structures of the concrete samples were not altered by addition of the nanoparticles (photocatalyst). Experimental results were compared to that found in previous literature and confirmed that the addition of 5% TiO2 did not affect the structure of the concrete samples and can be a viable option used in urban infrastructure such as permeable pavements.